PENGARUH AUDIT TENURE, INDEPENDENSI DAN PROFESIONALISME TERHADAP KUALITAS OPINI AUDIT (SURVEY PADA KANTOR AKUNTAN PUBLIK DI SURABAYA) - Mohammad Faris; M Nizarul Alim; Robiatul Auliyah (JAFFA, 2015)
The purpose of the study is to analyze and test the influence of tenure audit, independence and profesionalism on audit opinion quality both partially and simultaneously and also factors that influence audit opinion quality. Population used in the study is Public Accountant Offices in Surabaya.Samples collecting technique applied is simple random sampling. Samples are auditors that work on public accountant offices in Surabaya. Data collecting is conducted through questionnaire. The total of questionnaires distribute to auditors are 70 and the returned questionnaires are 62.The result of the study shows that audit tenure, independence and profesionalism variables simultaneously and significantly influence audit opinion quality. In partial, the value of audit tenure, independence and professionalism, and all of variable significantly influence the audit opinion quality.